AB0214 4-YEAR EXPERIENCE OF AN OUTPATIENT CLINIC OF PATIENTS WITH CLINICALLY SUSPECTED ARTHRALGIAS OF EVOLVING TO ARTHRITIS. (2nd June 2020) - Nuño, L.; Peiteado, D.; Monjo, I.; Villalva, A.; Novella-Navarro, M.; Miranda-Carus, M. E.; Fortea-Gordo, P.; Santos-Bornez, M. J.; De Miguel, E.; Balsa, A.
Abstract : Background: Although genetic and serological risk factors have been extensively studied in rheumatoid arthritis (RA), the phase of symptoms without clinical arthritis is poorly characterized. Objectives: To identify baseline clinical and immunological markers in patients with clinically suspicious arthralgia (CSA) progressing to chronic arthritis. Methods: Prospective longitudinal study of a cohort of patients with CSA. Patients are were followed up for at least 2 years, with clinical and analytical data collection by means of standardized protocols every 6 months. Inclusion criteria were an onset of symptoms ≤ 12 months, inflammatory arthralgias involving small joints of hands or feet (predominantly in nights or mornings, improving throughout the day or with movement, and morning stiffness ≥30 min). Patients with clinical synovitis, diagnosis of fibromyalgia or osteoarthritis at baseline visit were excluded from the study. Results: 45 patients were recruited from November 2015 in our CSA clinics. The majority were women (42 patients), with a mean age at entry of 44 ± 13 years, a mean duration of symptoms before entry of 32.3 ± 15.1 weeks, and a mean follow-up time of follow-up of 17.2 ± 13.3 months. A third (30%) of patients had a family history of autoimmune diseases, 18.6% were seropositive, an average body mass index (BMI) of 27.6 ± 6.6, and 14 (31.3%) were smokers or ex-smokers. Most patients reported a progression of arthralgia over time (53%) and a joint swelling (57%). Out of 45 patients, 18 (40%) developed clinical arthritis or autoimmune disease (11 RA, 2 undifferentiated arthritis, 3 spondyloarthritis, 2 undifferentiated connective diseases), after 7 ± 8.6 months of follow-up. Among patients with ≥ 6 months follow-up, 47.1% progressed to a clinical arthritis (CA). CA patients had a longer follow-up time (22.4 ± 13.9 vs. 16.8 ± 13 months; p = 0.015), and a higher frequency of smoking (60 vs. 21.7%; p = 0.037). Likewise, CA patients presented a higher age at baseline, family history of autoimmune disease and higher baseline scores of HAQ, PGA and VAS pain, although without statistical significance (Table 1 ). In the subset of patients with a final diagnosis of RA, patients presented a significantly longer follow-up, and higher scores of baseline VAS pain compared to non-progressors (Table 2 ). Conclusion: In our CSA clinic, 40% of the patients progressed to clinical arthritis, while almost half of those who were followed for more than 6 months progressed. PROs are important to consider as markers of future development of RA. It is necessary to expand the number of patients recruited to obtain more robust conclusions. Disclosure of Interests: Laura Nuño: None declared, Diana Peiteado: None declared, Irene Monjo: None declared, Alejandro Villalva: None declared, Marta Novella-Navarro: None declared, Maria-Eugenia Miranda-Carus Grant/research support from: BMS, Roche, Paula Fortea-Gordo Grant/research support from: BMS, Maria-Jose Santos-Bornez Grant/research support from: BMS, Eugenio de Miguel Grant/research support from: Yes (Abbvie, Novartis, Pfizer), Consultant of: Yes (Abbvie, Novartis, Pfizer), Paid instructor for: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Speakers bureau: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz